Foreign policy, sovereignty and individual rights of foreigners: the epilogue of the Battisti case in the light of a historical analysis of the jurisprudence of the STF (Supreme Federal Court) - Borges, Daniel Damasio [UNESP] (Centro de Ensino Unificado de Brasilia, 2022)
The way in which the Brazilian State directs and implements its foreign policy affects the individual rights of foreigners, especially in matters of expulsion and extradition. The recent STF decision on the Battisti case is an illustration of this. This case gives us the guiding thread to reflect on this relationship between foreign policy and individual rights. Throughout its history, the STF has adopted two notions of sovereignty in cases involving Brazilian foreign policy. The first is in the sense of a sovereignty limited by the Constitution, in which the rights of foreigners must be guaranteed. The second is in the sense of the unrestricted power of the Executive Branch, which cannot be controlled by the Judiciary Branch. The article seeks to analyze the STF judgments in which these two meanings appear. In order to carry out this analysis, a study of the STF’s jurisprudence was made, addressing historical cases on this issue since the first Republican Constitution of 1891. As we will try to demonstrate, if the first concept of sovereignty avoids arbitrary acts of the Executive Power, the second justifies.
Política externa, soberania e direitos individuais dos estrangeiros: o epílogo do caso Battisti à luz de uma análise histórica da jurisprudência do STF (Supremo Tribunal Federal)*
Keywords: expulsion; extradition; foreign policy; foreigners; individual rights; judicial review; sovereignty